TONGLING MUSIC INNOVATION WITH PRINGGOWULUNG WONOMULYO ART STUDIO, GENILANGIT, PONCOL, MAGETAN REGENCY - Darno Darno; Sutriyanto Sutriyanto; Sigit Setiawan (JURNAL PAKARENA, 2022)
Tongling musical instrument derived from the words "kentongan" and "suling" a musical instrument made of bamboo material, is an art originating from the Pringgowulung Wonomulyo art studio, Genilangit village, Poncol district, Magetan regency, East Java. Wonomulyo creates and can preserve the art of tongling until now, because tongling music is an accompaniment during worship so that it can survive until now, using Darsono's artistic creation approach, is expected to produce a craft work in the form of a musical instrument using large bamboo material as an accompaniment and complement of Tongling musical instrument that already exists